Parasites lacking the micronemal protein MIC2 are deficient in surface attachment and host cell egress, but remain virulent in vivo [version 2; referees: 1 approved, 2 approved with reservations] - Simon Gras; Allison Jackson; Stuart Woods; Gurman Pall; Jamie Whitelaw; Jacqueline M. Leung; Gary E. Ward; Craig W. Roberts; Markus Meissner (Wellcome Open Research, 2017)
Background: Micronemal proteins of the thrombospondin-related anonymous protein (TRAP) family are believed to play essential roles during gliding motility and host cell invasion by apicomplexan parasites, and currently represent major vaccine candidates against Plasmodium falciparum, the causative agent of malaria. However, recent evidence suggests that they play multiple and different roles than previously assumed. Here, we analyse a null mutant for MIC2, the TRAP homolog in Toxoplasma gondii. Methods: We performed a careful analysis of parasite motility in a 3D-environment, attachment under shear stress conditions, host cell invasion and in vivo virulence. Results: We verified the role of MIC2 in efficient surface attachment, but were unable to identify any direct function of MIC2 in sustaining gliding motility or host cell invasion once initiated. Furthermore, we find that deletion of mic2 causes a slightly delayed infection in vivo, leading only to mild attenuation of virulence; like with wildtype parasites, inoculation with even low numbers of mic2 KO parasites causes lethal disease in mice. However, deletion of mic2 causes delayed host cell egress in vitro, possibly via disrupted signal transduction pathways. Conclusions: We confirm a critical role of MIC2 in parasite attachment to the surface, leading to reduced parasite motility and host cell invasion. However, MIC2 appears to not be critical for gliding motility or host cell invasion, since parasite speed during these processes is unaffected. Furthermore, deletion of MIC2 leads only to slight attenuation of the parasite.